Genomic variability and plasticity of Pseudomonas causing coffee leaf spots in Minas Gerais state, Brazil. (27th December 2021) - Alves, Francisco Henrique Nunes da Silva; Monteiro, Ana Leticia Rocha; Pereira, Isadora Cristófoli; da Silva, José Cleydson Ferreira; Almeida, Renan N. D.; McTavish, Kathryn J.; Guttman, David S.; Raimundi, Melina Korres; de Souza, Ricardo Magela; de Resende, Mario Lucio Vilela; Badel, Jorge Luis
Abstract: Foliar spots caused by Pseudomonas coronafaciens pv. garcae (Pcg), Pseudomonas amygdali pv. tabaci (Pat) and Pseudomonas cichorii (Pch) are major bacterial diseases that can reduce coffee production. However, little is known about the genetic diversity and molecular mechanisms underlying the pathogenicity to coffee plants of these bacteria. In this study, genome sequences of Pcg, Pat and Pch strains isolated from coffee plants in Minas Gerais state, Brazil, were used to assess their variability and plasticity, and compare their type III secretion system (T3SS) and apoplastic effector repertoires as well as tabtoxin biosynthetic/detoxification genes. Genomic diversity was found for all three phytopathogens, among which Pch possesses the highest number of exclusive proteins. The Pcg genome is the most stable whereas that of Pch is the most plastic, which is related to their host ranges. When compared with those of Pseudomonas syringae pv. tomato DC3000, hrp / hrc gene sequences are more conserved in Pcg and Pat than in Pch, which also possesses the smallest T3SS and the largest apoplastic effector repertoires. The only T3SS effector family common to all three pathogens is AvrE, suggesting that, as for other plant– Pseudomonas interactions, it may play a crucial role for pathogenicity towards coffee plants. Apoplastic proteins associated with maintaining the redox balance and degrading proteins/peptides not previously described as important in plant–bacteria interactions were found. Gain/loss of the tabtoxin biosynthetic cluster with retention of the antitoxin gene was observed, indicating that tabtoxin production is not a limiting factor for the occurrence of mixed infections. Abstract : Phylogenomics, pangenomics and comparative genomics revealed genomic variability and plasticity of Pseudomonas that cause foliar spots in coffee plants, including effector and tabtoxin gene variation.